Energy saving potatoes digger - D. R. Norchaev (Сельскохозяйственные машины и технологии, 2016)
Mechanization of harvesting of potatoes takes root more widely everything around the world due tof potato-harvesting machines which allow to lower work expenses by 3-5 times. Because of soil and climatic features (high summer temperatures, low relative humidity of air, soil puddling) potato-harvesting machiness did not become widely used in the Republic of Uzbekistan. Therefore potato diggers KTN-2B and KST-1.4 are operated at harvesting with the assistance of numerous workers and loaders, that increases stoop labour. In the conditions of Uzbekistan when early potatoes harvesting during the summer period humidity of the soil is lowered. Therefore at digging the soil layer with tubers crumbles badly, with formation of large lumps that complicates separating them from tubers on a sizing screen and an elevator. It leads to increase in loss and damage of tubers. The production digging working tools of the existing potatoes diggers take away the excess soil in a significant amount at digging, and as a result tuberi mass build-up in front of a ploughshare. As result the harvestig becomse difficult and traction resistance increases. Therefore carrying out scientific researches on development of more effective method of tubers harvesting providing the demanded quality of work at smaller energy consumption and bigger productivity is required.The authors worked out the energy saving digger reducing losses and damages of potatoes tubers. Its outfit consists of basic clods breaking tools, undersized section ploughshares and a swathmaker. Results of power indicators were represented. Advantage of an energy saving potatoes digger in comparison with production machines were revealed during tests. The traction resistance of an energy saving potatoes digger and a consumption of petroleum, oil and lubricants decreased by 15-18 and 11 percent respectively, in comparison with a production digger. Thus the speed of the movement and tractive power increased by 30 and 20 percent respectively.